2021
DOI: 10.3390/molecules26175225
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Dynamics of Doxycycline and Gatifloxacin and Accumulation of Heavy Metals during Broiler Manure Aerobic Composting

Abstract: In this study, broilers were fed with heavy-metal-containing diets (Zn, Cu, Pb, Cr, As, Hg) at three rates (T1: 5 kg premix/ton feed, T2: 10 kg premix/ton feed and T3: 15 kg premix/ton feed) and Doxycycline (DOX) and Gatifloxacin (GAT) at low or high doses (T4: 31.2 mg DOX/bird/day and 78 mg GAT/bird/day, T5: 15.6 mg DOX/bird/day and 48 mg GAT/bird/day) to assess the accumulation of various heavy metals and the fate of two antibiotics in broiler manure after 35 days of aerobic composting. The results indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Thus, increasing composting temperature, extending high-temperature exposure, or increasing pH should facilitate antibiotic breakdown. However, heavy metals remained highly concentrated in the final composted product, which could potentially be transmitted to humans if applied as organic fertilizer [20].…”
Section: B Compostingmentioning
confidence: 99%
“…Thus, increasing composting temperature, extending high-temperature exposure, or increasing pH should facilitate antibiotic breakdown. However, heavy metals remained highly concentrated in the final composted product, which could potentially be transmitted to humans if applied as organic fertilizer [20].…”
Section: B Compostingmentioning
confidence: 99%
“…However, due to the use of additives in livestock and poultry breeding, an accumulation of heavy metals may exist in biogas residue, and studies have shown that the biological activities of Cu and Zn in biogas residue after composting treatment increases, and long-term return to farmland will cause potential pollution in the soil. Studies have shown that aerobic composting of biogas residue cannot eliminate and reduce the toxic effect of heavy metals [5,6]. After composting, heavy metal levels have not been effectively decreased, so it is urgent to add additives to adsorb and passivate heavy metals.…”
Section: Introductionmentioning
confidence: 99%